Binding properties of avian myeloblastosis virus DNA polymerases to nucleic acid affinity columns. - Grandgenett, D P (1975)
A new method for the analysis and purification of the RNA-directed DNA polymerase of RNA tumor viruses has been developed. This nucleic acid affinity chromatography system utilizes an immobilized oligo (dT) moiety annealed with poly (A). The alpha and alphabeta DNA polymerases of avain myeloblastosis virus bound effectively to poly (A) oligo (dT)-cellulose. Alpha DNA polymerase did not bind effectively to poly (A) oligo (dT)-cellulose, poly (A)-cellulose, or to cellulose. Alphabeta bound to oligo (dT)-cellulose and cellulose at the same extent (approximately 30%), indicating that this enzyme did not bind specifically to the oligo (DT) moiety only. However, alphabeta bound to poly (A)-cellulose two to three times better than to cellulose itself, showing that alphabeta could bind to poly (A) without a primer. Alphabeta DNA polymerase also bound to poly (C)-cellulose, whereas alpha did not. These data show that the alpha DNA polymerase is defective in binding to nucleic acids if the beta subunit is not present. Data is presented which demonstrates that the alphabeta DNA polymerase bound tighter to poly (A). oligo (DT)-cellulose and to calf thymus DNA-cellulose than the alpha DNA polymerase, suggesting that the beta subunit or, at least part of it is responsible for this tighter binding. In addition, alphabeta DNA polymerase is able to reversibly transcribe avian myeloblastosis virus 70S RNA approximately fivefold faster than alpha DNA polymerase in the presence of Mg2+ and equally efficient in the presence of Mn2+. alpha DNA polymerase transcribed 9S globin m RNA slightly better than alphabeta with either metal ion.